2018
DOI: 10.1109/tnsre.2018.2848845
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Framework for Quantitatively Connecting the Mechanical Design of Passive Prosthetic Feet to Lower Leg Trajectory

Abstract: This paper presents a novel framework that quantitatively connects the mechanical design of a prosthetic foot to its anticipated biomechanical performance. The framework uses kinetic inputs (ground reaction forces and center of pressure) to predict kinematic outputs of the lower leg segment by knowing the geometry and stiffness of the foot. The error between the predicted and target kinematics is evaluated using a root-mean-square error function called the Lower Leg Trajectory Error (LLTE). Using physiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 27 publications
0
24
0
Order By: Relevance
“…The LLTE value is then calculated as the error between the simulated and reference lower leg trajectory (Eq. 1) 18 . Here we extended the calculation of the LLTE metric from the portion of step where the foot is flat on the ground 19 , mid-stance, to the entire step by including the heel-strike and late-stance portions of a step (Fig.…”
Section: Calculation Of the Llte Valuementioning
confidence: 99%
See 1 more Smart Citation
“…The LLTE value is then calculated as the error between the simulated and reference lower leg trajectory (Eq. 1) 18 . Here we extended the calculation of the LLTE metric from the portion of step where the foot is flat on the ground 19 , mid-stance, to the entire step by including the heel-strike and late-stance portions of a step (Fig.…”
Section: Calculation Of the Llte Valuementioning
confidence: 99%
“…During mid-stance, the position and orientation of the lower leg are fully defined by the position of the CoP along the ground, the applied GRFs, and the prosthetic foot mechanical characteristics, assuming a no-slip condition and the foot to be tangent to the ground at the CoP location 18 (Fig. 1c).…”
Section: Calculation Of the Llte Valuementioning
confidence: 99%
“…Thus, roll-over geometry does not fully describe the functionality of a given prosthetic foot. Our previous work has demonstrated that it is possible for two different prosthetic feet to have identical roll-over geometries but yield very different lower leg kinematics under the same ground reaction forces (GRFs) [18][19][20]. Therefore, roll-over geometry is insufficient to be used in optimizing the design of prosthetic feet, as ideal kinematics cannot be ensured.…”
Section: Introductionmentioning
confidence: 99%
“…We have created a novel design objective, called the lower leg trajectory error (LLTE), that quantifies how closely the position of the lower leg segment for a given prosthetic foot is able to replicate target physiological lower leg position, in both space and time, throughout the course of a step [18][19][20]. LLTE is defined as…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation